Musculoskeletal pain associated with the use of computer systems in Nigeria - Adedoyin, Rufus A.; Idowu, Bimbo O.; Adagunodo, Rotimi E.; Owoyomia, Ayodeji A.; Idowu, Peter A. (IOS Press, 2020)
International Journal of Technology and Health Care, Vol. 13, p.125 – 130.